Book Review of "Hacking the Bomb: Cyber Threats and Nuclear Weapons" by Andrew Futter - Lopamudra Bandyopadhyay (International Journal of Nuclear Security, 2021)
A Professor of International Politics at the University of Leicester, UK, Professor Andrew Futter is indeed a significant name when it comes to the study of contemporary nuclear weapons, nuclear strategy, and arms control. He has had such seminal publications to his credit, like The Politics of Nuclear Weapons (London, SAGE: 2015) and Ballistic Missile Defence and US National Security: Normalisation and Acceptance after the Cold War (New York & Basingstoke, Routledge: 2013), as well as important edited books, such as Threats to Euro-Atlantic Security (London, Palgrave: 2019), The United Kingdom and the Future of Nuclear Weapons (New York, Rowman & Littlefield: 2016), and Reassessing the Revolution in Military Affairs: Transformation, Evolution and Lessons Learnt with Jeffrey Collins (London, Palgrave: 2015) – not to mention innumerable articles on nuclear weapons, nuclear deterrence, nuclear disarmament, cyber security, and cyber semantics. It is relevant to mention here that Professor Futter is a member of the cyber-nuclear security threats task force run by the Nuclear Threat Initiative, an Honorary Research Fellow in Nuclear Strategy at the Institute for Conflict, Cooperation and Security at the University of Birmingham, and a member of the Euro-Atlantic Security Initiative Next Generation working group. His academic stints at the Center for Arms Control and Non-Proliferation in Washington, D.C.; the James Martin Center for Nonproliferation Studies in Monterey, California; and the Norwegian Nobel Peace Institute in Oslo are also worth mentioning at the commencement of this book review.